De que verdade falou-se? : a oposição na administração de Arthur Ferreira Filho em Passo Fundo(1938-1947) - Silva, Adriana Ferreira da (2010)
This research studies the political career of Arthur Ferreira Filho in the administration of the City of Passo Fundo. His first administration was from March 1938 to December 1941, the second from October 1944 to November 1945 and the last in February 1946, after the end of the Estado Novo. During this period, the opponents of Ferreira Filho remained active in their comments and criticisms about the representative of the state dictatorship-novista through literature, they were curtailed by censorship. The book "Defending the Truth", published in 1947, under the poet and liberator Gomercindo dos Reis, denounced the actions of administrative Ferreira Filho with poetry and satire. After ten years of its first publication, he launched a second work entitled "Garden of Nettles" in 1957. In this are recorded a collection of critical verses referring to administrative acts, as well as political relations of Ferreira Filho with the opponents. This work will give us a reading of the Estado Novo, from the perspective of the opponents, in relation to the "Administrative Bambochata" from Ferreira Filho